Benign cystic peritoneal mesothelioma. Case report - Torres Cepeda, Duly (2016)
Benign peritoneal cystic mesothelioma is a rare benign tumor occurring in women of reproductive age. Acute presentation is even very rare and options of management are not established. A case of a 25-year-old woman with multiple episodes of hypogastric pain and dysmenorrheal is presented. Transvaginal US showed a cystic mass involving left flank to pelvis. The uterus and adnexae were congestive at laparoscopy. Both ovaries, Douglas sac and omentum had grape-like thin-walled cystic clusters. The patient was treated with total omentectomy and complete surgical resection of cysts. Histological analysis of the mass confirmed the diagnosis of benign peritoneal cystic mesothelioma.